2013
DOI: 10.1007/s00381-013-2310-6
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic determination of normal Conus Medullaris level and ascent in early infancy

Abstract: Rostral migration of CM level continues through the first few months of post-natal life, albeit of limited extent. Documentation of continued ascent in a neonate may obviate the need for magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Prenatal ascent of the conus, confirmed with MRI, continues for three months after a term birth . The conus terminates below L2 with decreasing frequency during the first 3 months in normal term infants: 13% in the first, 11% in the second, and 5% in the third month of life …”
Section: Presenting Clinical Findings and Evaluation Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Prenatal ascent of the conus, confirmed with MRI, continues for three months after a term birth . The conus terminates below L2 with decreasing frequency during the first 3 months in normal term infants: 13% in the first, 11% in the second, and 5% in the third month of life …”
Section: Presenting Clinical Findings and Evaluation Methodsmentioning
confidence: 87%
“…30 The conus terminates below L2 with decreasing frequency during the first 3 months in normal term infants: 13% in the first, 11% in the second, and 5% in the third month of life. 31 Therefore, conus termination below L2 after 3 months of age should raise suspicion for TSC, but diagnosing TSC solely based on conus level must be juxtaposed to age in preterm infants during early postnatal life. Determining conus level can be complicated by sacralization of lumbar vertebrae resulting in a higher normal conus position or lumbarization of sacral segments leading to lower conus termination.…”
Section: Imaging For Suspected Cases Of Osdmentioning
confidence: 99%
“…In the second group (gestational age: 40-63 weeks) this level was most often between T12/L1 and L1/L2. Zalel et al (2006) and Rozzelle et al (2014) also used ultrasound to assess the level of the normal conus medullaris in fetuses and infants. The former examined 110 fetuses and found that in all cases the conus medullaris was at the level of L4 between gestational weeks 13-18 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…At term, all fetuses showed the conus medullaris above the level of L2, with a distinct ascent between gestational weeks 13-40. Rozzelle et al (2014) conducted a retrospective review of more than a thousand lumbar ultrasounds of infants referred to a pediatric tertiary referral center. They found that the level of the conus medullaris ranged between T12 and L4, with the median corresponding with the L1/L2 interlaminar space.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) has the potential to increase LP success rates and decrease traumatic LPs but has not been adequately studied in pediatric patients. US can also help visualize the termination of the conus (which can range from the T12 to the L4 interspace in infants) in order to safely avoid the spinal cord . Two prior randomized trials showed promising results for US assistance compared to standard techniques for interspace selection.…”
mentioning
confidence: 99%